DEVELOPMENT OF LOW COST AND HIGH PRECISION PROTOTYPE SYSTEMS FOR MORPHOLOGICAL AND SEDIMENTARY DATA ACQUISITION IN SANDY SHORES - Baptista, Paulo; Cunha, Telmo; Bernardes, Cristina; Gama, Cristina; Ferreira, Óscar (My University, 2008)
In the scope of the INSHORE project (INtegrated System for High Operational REsolution in Shore Monitorisation), a low cost and high efficiency monitoring system is under development, being adequate for sandy shore surveying (from the foreshore to backshore), which integrates two prototype systems for morphological and sedimentary data survey. The first prototype system is a high resolution GPS based system incorporated on a four-wheel motor quad. This system allows the morphological survey of sandy beaches stretches with tens of kilometres in just a few hours, resulting on the production of 3D digital elevation models and respective characterisation of the main morphological features. The second prototype system is a digital image system for an automatic sand textural analysis, using image processing techniques. This system, when integrated with the former, allows a geo-referenced and real-time grain size textural analysis of a great number of samples along the sector under study.
Keywords: DGPS; Digita Elevation Model; monitoring system; sandy coasts